Novel Regulatory Factors in the Hypothalamic-Pituitary-Ovarian Axis of Hens at Four Developmental Stages - Li, Jing; Li, Chong; Li, Qi; Li, Guoxi; Li, Wenting; Li, Hong; Kang, Xiangtao; Tian, Yadong (Frontiers in Genetics, 2020)
Ovarian follicular development is an extremely complex and accurate process in which the hypothalamic-pituitary-ovarian (HPO) axis plays a crucial role. However, research on the regulatory factors of the HPO axis is sparse. In this study, transcriptomes of the tissues in the entire HPO axis at four ages (15 w, 20 w, 30 w, and 68 w of age) were analyzed. In total, 381, 622, and 1090 differentially expressed genes (DEGs) were found in the hypothalamus, pituitary, and ovary, respectively. In particular, the greatest number of DEGs (867) was obtained in the comparison at 30 w and 15 w in ovary, which might be involved in ovarian development and function at high ovulation capacity. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses indicated that most of these DEGs in the significantly enriched biological process (BP) terms and pathways were primarily involved in tissue development and the regulation of reproductive hormone biosynthesis and secretion. The latter is highly related to the HPO axis. Therefore, a number of hub candidate genes strongly associated with the HPO axis in each tissue were filtered by analyzing the Protein-protein interaction (PPI) network and seven known reproductive hormone-associated key genes were obtained: PGR, HSD3B2, CYP17A1, CYP11A1, CYP21A2, STS, CYP19A1, and 12 novel genes: ROCK2, TBP, GTF2H2, GTF2B, DHCR24, DHCR7, FDFT1, LSS, SQLE, MSMO1, CYP51A1, and PANK3 which would be utilized for further research on HPO axis function. The study highlighted the major role of the HPO axis in the reproduction of hens at the four developmental stages and explored the novel factors that might regulate reproduction, thus providing new insights into the function of the HPO axis on the reproductive system.